Four-step eco-friendly energy efficient recycling of contaminated Nd2Fe14B sludge and coercivity enhancement by reducing oxygen content - Syed Kamran Haider (Nature Portfolio, 2021)
Abstract Complete recycling of Nd2Fe14B sludge by chemical methods has gained significance in recent years, however, it is not easy to recycle highly contaminant sludge and obtain product with good magnetic properties. Herein we report a simple four-step process to recycle the Nd2Fe14B sludge containing ~ 10% of contaminants. Sludge was leached in H2SO4 and selectively co-precipitated in two steps. In the first co-precipitation, Al3+ and Cu2+ were removed at pH 6. Thereafter, in the second co-precipitation Fe2+ and RE3+ sulfates were converted to the Fe and RE hydroxides. By annealing at 800 °C RE and Fe hydroxides precipitates were converted to the oxides and residual carbon was oxidized to CO2. After the addition of boric acid, Fe and RE oxides were reduced and diffused to the (Nd-RE)2Fe14B by calciothermic reduction diffusion. Removal of CaO by washing with D.I. water in glove box reduced the oxygen content (~ 0.7%), improved crystallinity and enhanced the magnetic properties significantly. Coercivity increased more than three times (from 242.71 to 800.55 kA/m) and Mr value was also enhanced up to more than 20% (from 0.481 to 0.605 T). In this green process Na2SO4 and Ca(OH)2 were produced as by-product those are non-hazardous and were removed conveniently.